"Impact of age on management and prognosis of resuscitated sudden cardiac death patients". (June 2022) - Sans Roselló, Jordi; Vidal-Burdeus, Maria; Loma-Osorio, Pablo; Pons Riverola, Alexandra; Bonet Pineda, Gil; El Ouaddi, Nabil; Aboal, Jaime; Ariza Solé, Albert; Scardino, Claudia; García-García, Cosme; Fernández-Peregrina, Estefanía; Sionis, Alessandro
Graphical abstract: Sudden cardiac death in elderly people. IHCA: in-hospital cardiac arrest; NSE: neuron specific enolase; SSEP-N20: somatosensory evoked potentials N20; brain MRI: brain magnetic resonance imaging. Abstract: Background: Sudden cardiac death (SCD) has a great impact on healthcare due to cardiologic and neurological complications. Admissions of elderly people in Cardiology Intensive Care Units have increased. We assessed the impact of age in presentation, therapeutic management and in vital and neurological prognosis of SCD patients. Methods: We carried out a retrospective, observational, multicenter registry of patients who were admitted with a SCD in 5 tertiary hospitals from January 2013 to December 2020. We divided our cohort into two groups (patients < 80 years and ≥ 80 years). Clinical, analytical and hemodynamic variables as well as in-hospital management were registered and compared between groups. The degree of neurological dysfunction, vital status at discharge and the influence of age on them were also reviewed. Results: We reviewed 1160 patients admitted with a SCD. 11.3% were ≥ 80 years. Use of new antiplatelet agents, performance of a coronary angiography, use of pulmonary artery catheter and temperature control were less carried out in the elderly. Age, non-shockable rhythm, Killip class > 1 at admission, time to CPR initiation > 5 min, time to ROSC > 20 min and lactate > 2 mmol/L were independent predictors for in-hospital mortality. Non-shockable rhythm, Killip class > 1 at admission, time to CPR initiation > 5 min and time to ROSC > 20 min but not age were independent predictors for poor neurological outcomes. Conclusions: Age determined a less aggressive management and it was associated with a worse vital prognosis in patients admitted with a SCD. Nevertheless, age was not associated with worse neurological outcomes.